Effects of environment on sSFR profiles of late-type galaxies in the CALIFA survey - Coenda, Valeria (2019)
We explore the effects of environment on star formation in late-type galaxies by studying the dependence of the radial profiles of specific star formation rate (sSFR) on environment and the stellar mass, using a sample of 275 late-type galaxies drawn from the CALIFA survey. We consider three different discrete environments: Field galaxies, galaxies in pairs, and galaxies in groups, with stellar masses 9 ≤ log(M∗=M⊙) ≤ 12, and compare their sSFR profiles across the environments. Results. Our results suggest that the stellar mass is the main factor determining the sSFR profiles of late-type galaxies; the influence of AGNs and bars are secondary. We find that the relative size of the bulge plays a key role in depressing star formation towards the center of late-type galaxies. The group environment determines clear differences in the sSFR profiles of galaxies.We find evidence of an outside-in action upon galaxies with stellar masses 9 ≤ log(M∗=M⊙) ≤ 10 in groups. We find a much stronger suppression of star formation in the inner regions of massive galaxies in groups, which may be an indication of a different merger history.